Navigating university record management: guidelines and best practices / Nor Azliana Norli and Zakiah Mohd Noordin - Norli, Nor Azliana; Mohd Noordin, Zakiah (Faculty of Pharmacy, 2024)
In an era of increasing digitalization and information overload, effective record management is indispensable for universities to maintain operational efficiency, regulatory compliance, and historical continuity. The recent University Record Management Briefing held at the Faculty of Pharmacy, UiTM, provided crucial insights and guidelines on this vital aspect of administrative governance. The objectives of the program were clearly defined: to impart foundational knowledge of file and record management principles, delineate essential tasks involved in handling records, elucidate compliance requirements, ensure systematic implementation of record management standards, and foster adherence to established protocols.